Maksimalisasi Keuntungan Pada UMKM Sosis Bu Tinuk Menggunakan Metode Simpleks dan POM-QM - Dini Anggun Sari; Erna Sundari; Deshinta Dwi Rahmawati; Rudi Susanto (STMIK Budi Darma, 2020)
Today many people are competing in building businesses to meet their basic daily needs. Sausage trade business is one of the businesses in the culinary field. Of course, the traders doesn’t want a lost in their business. Therefore, traders must have the right technique or method to grow up and increased their business profits. This study is using the simplex method and supported by information technology that is POM-QM to estimating the maximum profit gained from each production which is made by sausage trader per day, so that it has an accurate calculation estimate. The calculation of maximum benefit is reaches in Rp 63.000,00 per day.